Prejudice and The New Latino Migration: The Geographic Locus of Anti-Latino Sentiment - Caraway, Angela (2010)
A large body of literature on the relationship between prejudice and discrimination and the size of minority populations suggests that as a minority population increases so will incidents of prejudice and/or discrimination. This school of thought is led by Hubert Blalock who contends that large minority populations generate prejudice among the majority, who view the minority as a threat to their economic and/or political standing. Minority population size has been tested and widely confirmed as a cause of anti-black prejudice and discrimination. But the corresponding research for Latinos has generally produced inconsistent and largely inconclusive findings. The reason for this confusion, according to this thesis, is that prior research has not accounted for a major turning point in the migration of Latinos. It is my contention that there are, in fact, two distinct Latino communities. One resides in the old and well-established immigrant communities that have been the destination of Latino migrants throughout the 20th century. But in recent years, Latino migrants settled in new destinations, in far-flung places, some very remote and generally lacking the social control benefits of old and well-established Latino enclaves. Thus, the link between anti-Latino sentiment and population size is more complex than previously considered. As such, my research produces four interrelated findings: 1) There is a positive relationship between percent change in the population of Latinos and resentment toward them among non-Latinos. 2) This effect exists in new Latino destinations, but not in old destinations. 3) The arrival of Latinos generates a broader resentment, not just toward Latinos specifically, but toward other minorities as well. These findings confirm the first three hypotheses. But the fourth finding does not support the final hypothesis. Specifically, my results do not confirm that anti-minority sentiment (in this case, toward Latinos) are rooted in competition over jobs. There is no significant link between the relative size of the low-skill labor market and anti-Latino prejudice. There are several implications of these findings